Wiedza z zakresu zagadnień prawnych w pracy pracownika socjalnego - Rajewska de Mezer, Joanna (Studia Edukacyjne, 2020)
This article raises the problem of the need to equip a social worker with knowledge concerning legal issues useful in assistance activities. Professional knowledge of selected legal problems is necessary in the face of still emerging new situations that create dysfunction for collective life and cause inability in overcoming difficultiesby using their own capabilities, competences and resources. Work aimed at supporting and activating a social welfare beneficiaryrequire from a social worker a wide interdisciplinary knowledge, including familiarity with various fieldsof law. Knowledge in the fieldof substantive (social law, family law) and procedural law used during work with a beneficiaryal-lows a social worker to conduct the assistance process more effectively. The law-realted problems faced by the social worker who performs statutory tasks are connected to the extent of the regulated problems, constant changeability of legal regulations, their interpretative ambiguity, the necessity of using judicial decisions. It requires appropriate, methodical and purposeful action in the process of educating social workers, which influences theexpected efficiency of theirwork and a sense of safety from a formal point of view.